Mengelola Nilai-Nilai Toleransi Dalam Kemajemukan Agama Di Desa Sukoreno Kecamatan Umbulsari Kabupaten Jember - Zainuri, Ahmad; Maulidia, Firda; Amrullah, M. Kholis (Universitas Islam Negeri Raden Intan Lampung, 2022)
Managing the values of tolerance in religious pluralism is an act that builds harmony among religious believers. Especially in Sukoreno Village which is a village with various religions in it, so how can the community take a role in any side with the aim of building harmony without hate speech. The management of the values of tolerance and harmony is one of the factors in the formula for the harmonious life of the Sukoreno community. The methodology in this study the author uses a qualitative research design with the concept of a case study, precisely in Sukoreno Village. The approach we use is a historical, social and religious approach. From the research, it is found that the social relations of Sukoreno's life are very harmonious and harmonious. Because in establishing a pluralistic life among religious people in Sukoreno Village, they instill values of tolerance to each other to build religious pluralism into religious harmony. The values of tolerance applied in the life of the Sukoreno community bring an inclusive impact on the existence of religions in Sukoreno Village, including the role of religious leaders and the Sukoreno Village community. Many forms of activities are carried out by the community together in realizing an inclusive and peaceful Sukoreno. They respect each other, help and respect each other in living a social life, regardless of background and background, all of which is done with the aim of maintaining inter-religious harmony in Sukoreno Village.